Peningkatan Pemahaman Keagamaan Melalui Pembelajaran Al-Qur’an di Dusun Sempu Desa Gadingkulon Kecamatan Dau Kab. Malang - Mustofa, Syaiful; Desrani, Ayu; Febriani, Suci Ramadhanti (JRCE (Journal of Research on Community Engagement), 2022)
This study aims to increase religious understanding through learning the Qur'an in Sempu Hamlet, Gadingkulon Village, Dau District, Malang Regency. This study uses a Participatory Action Research (PAR) approach, the sampling technique uses purposive sampling and the data analysis technique used is triangulation, the research methods used are observation, documentation, and interviews. Based on the results obtained from this service activity, namely; First, this activity resulted in approximately 80 children and 40 adults practiced reading and understanding the Qur'an in Surah Al-Fatihah and Surah Yasin fluently and correctly. Second, the socialization of learning the Koran, especially the letter al-Fatihah and the letter Yasin is an effort to increase the understanding of the diversity of the community in Sempu Hamlet, Gadingkulon Village, Dau District. Malang in the framework of community service programs. From the survey conducted, it is known that all participants feel that this activity is important, according to their needs and provides benefits for their lives. And the majority of participants (90%) stated that they would continue this activity even though formally this activity had ended.